FDI and economic growth: new evidence on the role of financial markets - Wan Ngah, Wan Azman Saini; Law, Siong Hook; Ahmad, Abd Halim (Elsevier, 2010)
This study uses a threshold regression model and finds new evidence that the positive impact of FDI on growth “kicks in” only after financial market development exceeds a threshold level. Until then, the benefit of FDI is non-existent.